National Leprosy Eradication Programme (NLEP) - Shetty Sushant; Shetty J N (Wolters Kluwer Medknow Publications, 1997)
This article traces the history of the growth and development of our National Leprosy Eradication Programme (NLEP). The aims, strategy, means of eradication, the organizational structure have been discussed. Since the beginning of this programme, the prevalence rate and disability rate have shown a sharp decline. The number of cases detected and under treatment have also increased. The achievement made has been possible due to an excellent organization of leprosy relief work under NLEP with the active cooperation of the non- governmental organizations. Now that leprosy is on the decline, the need of education and rehabilitation of patients assumes a greater importance.